AN ANALYSIS OF INTRINSIC ELEMENT IN EMILY DICKINSON’S “BECAUSE I COULD NOT STOP FOR DEATH” - Rahayu, Suci (LANTERN (Journal on English Language, Culture and Literature), 2016)
The writer discusses the intrinsic element in poetry of Emily Dickinson entitled “Because I Could Not Stop For Death”. The purpose of this study is to understand the intrinsic elements on the poem. The methods used were library research. By using the method of library research the writer collected some information and documents that support the process of analysis. The result of the study shows what kind of intrinsic elements is used in the poetry to deliver the message.